Principles for modelling dose-response for the risk assessment of chemicals : first draft prepared by the WHO Task Group on Environmental Health Criteria on Principles for modelling dose-response for the risk assessment of chemicals (WHO, 2009)
This volume is part of the ongoing review of the underlying scientific bases for decision-making in chemical risk assessment by International Programme on Chemical Safety. It involves specific consideration of the area of dose–response assessment in the evaluation of information from toxicological studies in animals and from human clinical and epidemiological studies. It covers toxicants with threshold effects and those for which there may be no practical threshold, such as substances that are genotoxic and carcinogenic. The discussions are concerned with that subset of cause–effect relationships commonly referred to as dose–response models, which are typically used to characterize the biological effects of intentional (e.g. drugs and nutrients) and unintentional (e.g. contaminants) exposure to chemicals.This report is intended primarily to provide descriptive guidance for risk assessors in using dose–response modelling in hazard characterization. It will also provide mathematical modellers with an appreciation of issues to be considered when modelling in the context of the risk assessment process. Risk managers will be able to obtain a general understanding of the applications and limitations of dose–response modelling. For both risk assessors and risk managers, some considerations for communicating the results of risk assessments that use dose–response modelling are presented.
Environmental health criteria, ISSN 0250-863X 239
Keywords: Chemical Actions and Uses; nebezpečné látky; Risk Assessment; Hazardous Substances; hodnocení rizik; Environmental Exposure; chemie, klinická chemie; environmentální vědy; vystavení vlivu životního prostředí; chemické látky - účinky a užití